Negativity: space, politics and affects. (January 2022) - Dekeyser, Thomas; Secor, Anna; Rose, Mitch; Bissell, David; Zhang, Vickie; Romanillos, Jose Luis
This paper reflects on the status of 'negativity' in contemporary social and geographical thought. Based on a panel discussion held at the American Association of Geographers Annual Meeting 2021, each contributor discusses what negativity means to them, and considers its various legacies and potential future trajectories. Along the way, the contributors offer ways of attending to negative spaces (voids, abysses, absences), affects (vulnerabilities, sad passions, incapacities, mortality) and politics (impasses, refusals, irreparabilities). However, rather than defining negativity narrowly, the paper stays with the diversity of work on negativity being undertaken by geographers and other scholars, discussing how varying perspectives expand or dismantle particular elements within spatial theory. Collectively, the contributors argue for paying attention to negativity as the faltering, failure or impossibility of relations between body and world, thus situating it in conversation with relational thought, vitalist philosophies and affirmative ethics.